Giant swings with turns completed to handstand on uneven bars - Thomas, K.; Bradshaw, E. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study investigated the technical features of successful turn to handstand performance during giant swinging skills on the uneven bars in Women's artistic competition. The uneven bar performances of the top five nations at the 2010 Pacific Rim Championships was videoed from the side. All giant and Stalder turn performances, 1800 'blind change' and 3600 'blind full', were assessed post competition to identify the discrete angles at turn start, the first hand grip change, and turn end. The turn end position was also judged using Article 7.4.4 of the Code of Points to determine any execution deductions. The turn start position for the four skills analysed suggest that there may be an optimum angle window for the turn start of 50-600, with the position of the first hand release largely dependent on the swing skill and the turn displacement required.